Exploring EFs and Math Abilities in Highly Deprived Contexts - Pellizzoni, Sandra; Apuzzo, Gian Matteo; De Vita, Chiara; Agostini, Tiziano; Ambrosini, Miriam; Passolunghi, Maria Chiara (Frontiers in Psychology, 2020)
Executive functions (EFs)’ development is critically affected by childhood adversity exposure. Although recent studies underlined the deleterious effects of early life stresses on working memory (WM) and inhibitory control, they were scarcely investigated in war context especially in relation with learning abilities. In order to fill this gap, we designed a research with the aim to evaluate EFs together with early math skills. In particular, we conducted a study involving 150 children divided into three groups: 48 Yazidis (Mage = 71 months, SD = 6.59), 47 Syrian refugees (Mage = 68.77 months, SD = 7, age), and 55 Italians (Mage = 68.65 months, SD = 2.88) attending the third year of kindergarten in Italy or inserted in Psyco-Social-Support activities in Iraq. The children were evaluated with a variety of tasks assessing WM, inhibitory control, counting, digit-quantity mapping, and digit naming skills. The results indicated substantial differences both in EFs and early numerical abilities between the deprived groups and the Italian children. Data are discussed in terms of implications for children both exposed to mainstream school environments and living in socio-economically disadvantaged and deprived contexts.